Live migration based on the characteristics of operation stages for virtual machine - xin ZOUQing; yu HAOZhi; chun YUNXiao (Tongxin xuebao)
Being directed against the different characteristics of start, iterative and end stages of pre-copy algorithm, live migration based on the characteristics of operation stages referred to as LMCOS was proposed. In the start stage, the technique of comparing initial memory page and sending variables was brought to avoid the transferring of unmodified memory. During the iterative stage, the transmitting method of counting sort was brought to reduce retransmitting mem-ory pages. In the end stage, the police of reducing time slices of virtual machine's CPU was brought to shorten the down-time. Compared with pre-copy algorithm, LMCOS reduces downtime by 53% and total migration time by 65% on average.